The mathematical model of resonant frequency converter with pulse regulation - Pavlov, H. V.; Vinnychenko, I. L.; Павлов, Г. В.; Вінниченко, І. Л. (My University, 2018)
On the basis of the state variables method, the mathematical model of the resonant converter is constructed, within which the analytical dependences are obtained, which allow calculating the durations of the inter-commutation stages, the certain sequence of which provides the sinusoidal shape of the carrier pulses. The article aim is to study electromagnetic processes in the power section of the resonant frequency converter with pulse control and to obtain the analytical expressions for the durations of the inter-commutative stages of the converter operation. With the usage of the state variables method, the solutions of vector-matrix equations, which describe the processes in the power section of the resonant frequency converter, were obtained. That made possible to get the exact shape of the resonant voltage and current pulses and determine the durations of the inter-commutation stages, which provide their shape, characterized with the low THD. The phase characteristic of the converter operation cycle is constructed as well. The results of the research can be applied in the development of the pulse frequency converters control systems. The obtained analytical expressions allow computing the required switching moments of the converter power transistors.
Математична модель резонансного перетворювача частоти з імпульсним регулюванням
Pavlov, H. V. The mathematical model of resonant frequency converter with pulse regulation = Математична модель резонансного перетворювача частоти з імпульсним регулюванням / H. V. Pavlov, I. L. Vinnychenko // Shipbuilding & Marine Infrastructure. – 2018. – № 1 (9). – P. 21–28.
Keywords: frequency converter; resonant inverter; mathematical model; state variables method; phase characteristics; дволанковий перетворювач частоти; резонансний інвертор; математична модель; метод змінних стану; фазові діаграми